The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9ra05439a
|View full text |Cite
|
Sign up to set email alerts
|

A room temperature operated ammonia gas sensor based on Ag-decorated TiO2 quantum dot clusters

Abstract: In this research, nanometer size aggregates (clusters) of titanium dioxide (TiO2) quantum dot clusters (QDs) have been successfully prepared via a convenient hydrolysis method at a low temperature (80 °C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Among a wide variety of metal oxides, TiO 2 is a promising material for many emerging applications, such as gas sensors [1,2], dye-sensitized solar cells [3,4], photocatalysis [5] and gate insulators in metal-oxide-semiconductor field-effect transistors [6]. The characteristics of TiO 2 thin films prepared by sol-gel, chemical vapor deposition or sputtering have been extensively studied [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among a wide variety of metal oxides, TiO 2 is a promising material for many emerging applications, such as gas sensors [1,2], dye-sensitized solar cells [3,4], photocatalysis [5] and gate insulators in metal-oxide-semiconductor field-effect transistors [6]. The characteristics of TiO 2 thin films prepared by sol-gel, chemical vapor deposition or sputtering have been extensively studied [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the above sections, we have described the effect of Ag decoration on the gas response of resistive-based gas sensors. Table 1 [48][49][50][51][52]54,60,65,66,69,70,72,74,76,77,80,[85][86][87][88][89][90][91][92][93][94][95] shows the gas-sensing performances of Ag-loaded SMO-based sensors for various toxic gases. In addition, other researchers [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] have reported enhanced gas sensing after Ag decoration.…”
Section: Summary Of Ag-decorated Gas Sensorsmentioning
confidence: 99%
“…Table 1 [48][49][50][51][52]54,60,65,66,69,70,72,74,76,77,80,[85][86][87][88][89][90][91][92][93][94][95] shows the gas-sensing performances of Ag-loaded SMO-based sensors for various toxic gases. In addition, other researchers [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] have reported enhanced gas sensing after Ag decoration. Depending on the type of SMO and the synergistic effects between Ag and SMO, the sensing temperature can vary from room temperature to high temperatures.…”
Section: Summary Of Ag-decorated Gas Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [14] have studied WO 3 nanofibers for ammonia gas detection at an operating temperature of 623 K. Wu et al [15] reported an ammonia sensor based on graphene/PANI nanocomposite with a response of about 11 for 100 ppm. Liu et al [16] have studied the Ag-decorated Titanium oxide quantum dot clusters for ammonia detection at room temperature. Recently Wang et al [17] have investigated the gas sensing performance of closely packed WO 3 microspheres for ammonia detection with a response of 3.2 towards 100 ppm ammonia.…”
Section: Introductionmentioning
confidence: 99%